Canola meal as a source of feedstuff in formulated diets for broiler production after incorporation with digestive enzymes - Irani, Mehrdad; Ilia, Nima; Yousefian, Mehdi; Abedi, Hasan; Gharaveysi, Sahahabodin (The Indian Journal of Animal Sciences, 2012)
This study was conducted to evaluate effects of using Canola meal as a substitute to soybean meal in diets for broiler production. Male broiler chicks (720) were allocated to 16 treatments. The factors were canola level (0, 7.5, 15 and 22.5%) with combination of 4 levels of commercial enzyme (0, 90, 180 and 270 mg/kg). On the basis of growth response, food conversion ratio, 22.5% canola meal incorporated in the diet resulted in the best performance of broiler but was not significantly higher than control. Growth and feed utilization efficiencies of chicks fed canola meal containing enzyme of 180 mg/kg were superior to those fed diets containing lower canola and lower enzyme. The feed intake in 22.5% of canola was significantly higher than control, but the weight gain did not show the difference. It means by extra feeding of chicks on canola and using appropriate enzyme the reduction in weight will be compensated, however the growth rate for canola meal was lower at all levels of inclusion in comparison to those for the zero canola meals. The main effect of all enzyme level was not significant on feed intake, body weight gain and feed conversion ratio. There was no significant difference among treatments in dressing percentage, pancreas, abdominal fat, breast, thighs and legs ash percentage. The present results indicated that supplementation of canola diet with commercial enzyme 15 000 improved feed digestion in chicks. It was suggested that the optimum enzyme dose was about 180 mg / kg of feed.